Ace2 polymorphism: the human key for covid-19 severity - Noorizhab, Mohd Nur Fakhruzzaman; Shahlan Kasim, Sazzli; Mohd Nor, Fadzilah; Kek, Teh Lay; Salleh, Mohd Zaki (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
COVID-19, caused by the novel coronavirus SARS-CoV-2, has rapidly evolved into a global pandemic, profoundly impacting public health, economies, and societies worldwide. The disease's variable clinical manifestations range from asymptomatic cases to severe respiratory distress, highlighting the critical need to understand the genetic underpinnings of COVID-19 susceptibility and severity. This study aims to investigate the association between ACE2 gene polymorphisms and COVID-19 susceptibility and severity, providing insights that could be pivotal for developing targeted preventive and therapeutic strategies. ACE2, a transmembrane protein, is recognized as the primary entry point for SARS-CoV-2 into host cells. It is expressed in various tissues, including the lungs, heart, kidneys, and intestines, suggesting its central role in the multi-organ impact of the virus. Genetic variations in the ACE2 gene have been implicated in influencing an individual's susceptibility to and severity of COVID-19. Such variations can affect ACE2 expression levels or alter the protein's structure, potentially influencing the virus's ability to bind and enter cells. To elucidate these associations, we conducted a comprehensive genome mining analysis of 203 genomes from individuals diagnosed with COVID-19. Our analysis focused on identifying ACE2 polymorphisms associated with the disease. We analyzed a comprehensive set of 22 genetic markers across 15 genes linked to COVID-19 susceptibility from existing literature. These markers were chosen based on their documented association with immune response, viral entry mechanisms, and inflammatory processes in viral infections. Individuals were stratified into one of seven risk categories based on their genetic profiles: “Moderately increased infection risk”, “Moderately reduced infection risk”, “Roughly average infection risk”, “Slightly increased infection risk”, “Slightly reduced infection risk”, “Very slightly increased infection risk”, and “Very slightly reduced infection risk”. This stratification provides a nuanced understanding of individual variability in COVID-19 susceptibility, which could be critical for personalized risk assessment and management. We further explored the association between ACE2 polymorphisms and COVID- 19 severity. Our analysis extended to 42 genetic markers across 29 genes associated with COVID-19 severity, derived from available literature. These genes are involved in pathways like cytokine signaling, immune regulation, and cellular stress response, all of which are crucial in the pathogenesis of severe COVID-19. Among these markers, 12 (rs11385942, rs2082940, rs2248690, rs4444903, rs324420, rs1801274, rs4073, rs20541, rs2275913, rs832582, rs6721961, and rs3025039) were found to be present in at least 10% of the studied population and were associated with a higher risk of severe COVID-19 complications. Our findings suggest that ACE2 gene polymorphisms play a significant role in determining COVID-19 susceptibility and severity. Individuals harboring specific ACE2 genotypes may have an increased risk of developing COVID-19 and experiencing severe complications. This study underscores the importance of genetic factors in COVID-19 and opens avenues for personalized medicine approaches. The identification of high-risk genetic profiles can aid in early intervention strategies and tailored treatment plans, potentially improving patient outcomes. Furthermore, these findings have broader implications for public health policies and pandemic preparedness. Understanding genetic susceptibility can enhance screening strategies and inform vaccine distribution priorities. Additionally, our study lays the groundwork for future research exploring the interaction between ACE2 polymorphisms and other genetic or environmental factors contributing to COVID-19 outcomes. In conclusion, this study provides compelling evidence of the role of ACE2 gene polymorphisms in COVID-19 susceptibility and severity. By offering a more detailed genetic landscape of the disease, our research contributes significantly to the ongoing efforts to combat the COVID-19 pandemic through precision medicine and personalized healthcare strategies.